Linear ubiquitination by LUBEL has a role in Drosophila heat stress response. (4th October 2016) - Asaoka, Tomoko; Almagro, Jorge; Ehrhardt, Christine; Tsai, Isabella; Schleiffer, Alexander; Deszcz, Luiza; Junttila, Sini; Ringrose, Leonie; Mechtler, Karl; Kavirayani, Anoop; Gyenesei, Attila; Hofmann, Kay; et al.
Abstract: The HOIP ubiquitin E3 ligase generates linear ubiquitin chains by forming a complex with HOIL‐1L and SHARPIN in mammals. Here, we provide the first evidence of linear ubiquitination induced by a HOIP orthologue in Drosophila . We identify Drosophila CG11321, which we named Linear Ubiquitin E3 ligase (LUBEL), and find that it catalyzes linear ubiquitination in vitro . We detect endogenous linear ubiquitin chain‐derived peptides by mass spectrometry in Drosophila Schneider 2 cells and adult flies. Furthermore, using CRISPR/Cas9 technology, we establish linear ubiquitination‐defective flies by mutating residues essential for the catalytic activity of LUBEL. Linear ubiquitination signals accumulate upon heat shock in flies. Interestingly, flies with LUBEL mutations display reduced survival and climbing defects upon heat shock, which is also observed upon specific LUBEL depletion in muscle. Thus, LUBEL is involved in the heat response by controlling linear ubiquitination in flies. Synopsis: The HOIP ubiquitin E3 ligase generates linear ubiquitin chains in mammals and is implicated in immune signaling. This study identifies Drosophila LUBEL as HOIP orthologue, which catalyzes the formation of linear ubiquitin chains in flies and has a role in heat shock response. LUBEL is the major ubiquitin E3 ligase that specifically catalyzes linear ubiquitin chains (M1) in flies. LUBEL is sufficient to catalyze linear ubiquitination via a RING/HECT hybrid mechanism. Catalytically dead LUBEL mutant adult flies show impaired heat shock response. dCYLD interacts with LUBEL to remove linear and K 63‐linked ubiquitin chains. Abstract : The HOIP ubiquitin E3 ligase generates linear ubiquitin chains in mammals and is implicated in immune signaling. This study identifies Drosophila LUBEL as HOIP orthologue, which catalyzes the formation of linear ubiquitin chains in flies and has a role in heat shock response.